A new performance assessment of 5 GHz IEEE 802.11n four-node point-to-multipoint links - Carvalho, José Pacheco de (2019)
The performance of wireless communications is an essential point, leading to more trusty and efficacious communications. Security is also important. Laboratory experiments were performed on various performance points of Wi-Fi 5 GHz IEEE 802.11 n Open four-node point-to-multipoint links. Our study contributes to the performance assessment of this technology, utilizing accessible equipments (V-M200 access points from HP and WPC600N adapters from Linksys). New elaborated results are given and discussed, essentially at OSI levels 4 and 7, from TCP and UDP experiments: TCP throughput versus TCP packet size; jitter and percentage datagram loss versus UDP datagram size. Comparisons are made to correspondent results from Open point-to-point links. Conclusions are taken about the comparative performance of the links. © 2017 Institute of Measurement Science SAS.